Ovarian Reserve Assessment in Users of Oral Contraception Seeking Fertility Advice on their Reproductive Lifespan. Issue 2 (February 2016) - Birch Petersen, K.; Hvidman, H. W.; Forman, J. L.; Pinborg, A.; Larsen, E. C.; Macklon, K. T.; Sylvest, R.; Nyboe Andersen, A.
Abstract : Obstet Gynecol Surv 2016;71(2):84–85 Over the past 4 decades, European women (as well as American women) with no known fertility problem have been postponing their first pregnancy until 30 years or older. There has been increasing demand by these women for ovarian reserve testing and counseling to obtain estimates on their remaining reproductive life span.